Inhibitors of heat shock protein 70 (Hsp70) with enhanced metabolic stability reduce tau levels. (1st June 2021) - Shao, Hao; Li, Xiaokai; Hayashi, Shigenari; Bertron, Jeanette L.; Schwarz, Daniel M.C.; Tang, Benjamin C.; Gestwicki, Jason E.
Graphical abstract: Highlights: Two series of YM-08 analogs were designed to remove metabolic liabilities. Optimization resulted in JG-23, which is 12-fold more metabolically stable. Compound JG-23 reduced total tau in two cell-based models. Abstract: The molecular chaperone, Heat Shock Protein 70 (Hsp70), is an emerging drug target for neurodegenerative diseases, because of its ability to promote degradation of microtubule-associated protein tau (MAPT/tau). Recently, we reported YM-08 as a brain penetrant, allosteric Hsp70 inhibitor, which reduces tau levels. However, the benzothiazole moiety of YM-08 is vulnerable to metabolism by CYP3A4, limiting its further application as a chemical probe. In this manuscript, we designed and synthesized seventeen YM-08 derivatives by systematically introducing halogen atoms to the benzothiazole ring and shifting the position of the heteroatom in a distal pyridine. In microsome assays, we found that compound JG-23 has 12-fold better metabolic stability and it retained the ability to reduce tau levels in two cell-based models. These chemical probes of Hsp70 are expected to be useful tools for studying tau homeostasis.